Двовимірні узагальнені моментні зображення та раціональні апроксимації функцій двох змінних - Голуб, А.П.; Чернецька, Л.О. (Український математичний журнал, 2013)
Метод обобщенных моментных представлений В. К. Дзядыка распространен на случай двумерных последовательностей и применен к построению аппроксимаций Паде функций двух переменных. The Dzyadyk method of generalized moment representations is extended to the case of two-dimensional sequences and used to construct Padé approximants for functions of two variables.